Adsorption of volatile organic compounds onto activated carbon - Low, Chun Lai. (2009)
It is the porosity within activated carbon which imparts their dominant characteristics of adsorption. Adsorption arises as a result of the unsaturated and unbalanced molecular forces that are present on the solid surface. Thus, when a solid surface is brought into contact with a liquid or gas, there is an interaction between the fields of forces of the surface and that of the liquid or the gas. The solid surface tends to satisfy these residual forces by attracting and retaining on its surface the molecules, atoms, or ions of the gas or liquid. There are two types of adsorption which are physisorption and chemisorption that involve different forces. One of the useful applications of activated carbons is gas purification, for instance removal of VOCs. By using Thermogravimetric Analyzer (TGA) the adsorption behavior of the activated carbon can be investigated. Sample activated carbon is put inside the TGA and VOCs’ vapors are flowed into the furnace unit, any adsorption of vapors will give rise to the weight gain in the activated carbon itself. The concentration of the VOCs’ vapors and the specific surface area, SBET of the activated carbon are the determinant factors that affect the adsorption rate. Higher concentration of vapors will increase the adsorption amount of the activated carbon; while, larger SBET means larger space for more amount of adsorption.